2018
DOI: 10.1159/000492918
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Adherence in the Treatment of Secondary Hyperparathyroidism

Abstract: Secondary hyperparathyroidism (SHPT) is a frequent condition in the presence of chronic kidney disease (CKD). In CKD patients, SHPT is reported to increase both morbidity and mortality, especially cardiovascular. The difficulty in the treatment of SHPT in clinical practice is frequently encountered from a not always adequate conduct of the clinicians and a common non-compliance to the therapy of CKD patients. In this review, the greatest difficulties from clinicians and CKD-patients’ point of view in the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…This study demonstrated a good correction of n-hVITD, a good effect on PTH, and a safe profile for oral ER calcifediol [20]. This formulation might in the future solve the problems of the adherence to the 25(OH)VitD therapy, burdened by the drop formulation and by the unusual assumption schemes prescribed [21]. Independently of the native form of vitamin D used, clinicians should pay close attention to vitamin D toxicity, avoiding too high levels of plasmatic 25(OH)VitD, and monitoring calcium and phosphorus levels.…”
Section: Native Hypovitaminosis D During Chronic Kidney Disease (Cmentioning
confidence: 96%
“…This study demonstrated a good correction of n-hVITD, a good effect on PTH, and a safe profile for oral ER calcifediol [20]. This formulation might in the future solve the problems of the adherence to the 25(OH)VitD therapy, burdened by the drop formulation and by the unusual assumption schemes prescribed [21]. Independently of the native form of vitamin D used, clinicians should pay close attention to vitamin D toxicity, avoiding too high levels of plasmatic 25(OH)VitD, and monitoring calcium and phosphorus levels.…”
Section: Native Hypovitaminosis D During Chronic Kidney Disease (Cmentioning
confidence: 96%
“…Most patients with chronic renal failure (CRF), especially in developing countries, develop into secondary hyperparathyroidism (SH) if they do not receive advanced and appropriate professional treatment in the early stage of the disease (1)(2)(3). These patients had elevated serum phosphorus levels and decreased calcium levels.…”
Section: Introductionmentioning
confidence: 99%
“…These patients had elevated serum phosphorus levels and decreased calcium levels. SH produces a group of syndromes with abnormal facial appearance, which was first summarized and named as Sagliker syndrome (SS) by Dr. Sagliker of Turkey in 2004 (3,4). SS patients with short stature or shorter than before,…”
Section: Introductionmentioning
confidence: 99%
“…For commercial re-use, please contact journals.permissions@oup.com patients who are not adherent with the prescribed treatment schedule. The problem of treatment adherence therefore plays a crucial role in CKD-MBD therapy [8].…”
mentioning
confidence: 99%
“…Thus, as with most medicinal products, the efficacy of a phosphate binder is poorer in patients who are not adherent with the prescribed treatment schedule. The problem of treatment adherence therefore plays a crucial role in CKD-MBD therapy [ 8 ].…”
mentioning
confidence: 99%